(untitled) (UNED Research Journal, 2017)
Pleopeltis pleopeltifolia (Raddi) Alston is first cited for Buenos Aires province (Argentina). Furthermore, we provide new collecting sites for Pleopeltis minima (Bory) J. Prado & R.Y. Hirai and P. macrocarpa (Bory ex Willd.) Kaulf. Species that motivate this article characterize Mesopotamia gallery forests. They seem to be expanding their geographical distribution southwards, like other vascular plants and animals from the Platense area of the province. To prove if this shift can be attributed to the climate change, the advance distance of these taxa and other plants recently registered south from their previously known distribution was measured in three sites of northeastern Buenos Aires. This distance was compared with the shift of the isohyets and isotherms. The correlation between the biogeographic shift and the trend of climate change in the region is highlighted.